Peran Digital Marketing dan Harga Terhadap Keputusan Pembelian Batu Alam - Rizal Mustofa; Halimah Zahrah (Indonesia Economic Journal, 2026)
The rapid development of information and communication technology has led to significant changes in marketing strategies, particularly through the implementation of digital marketing. Digital marketing enables companies to reach consumers more widely, quickly, and efficiently, and plays an important role in influencing purchasing decisions. This study aims to analyze the effect of digital marketing and price on consumer purchasing decisions of natural stone products at Jibalstones. This research employs a quantitative approach, with data collected through questionnaires distributed to Jibalstones consumers. The data were analyzed using multiple linear regression analysis to examine the influence of each variable. The results indicate that digital marketing has a positive and significant effect on purchasing decisions, suggesting that effective utilization of digital platforms can increase consumer interest and trust. In addition, price also has a significant effect on purchasing decisions, where consumers tend to choose products with competitive prices that are proportional to the quality offered. Simultaneously, digital marketing and price have a significant influence on consumer purchasing decisions. These findings are expected to provide insights for companies in formulating effective digital marketing strategies and appropriate pricing policies to enhance competitiveness and increase sales of natural stone products.